The Dual Role of Hepcidin in Brain Iron Load and Inflammation - Vela, Driton (Frontiers in Neuroscience, 2018)
Hepcidin is the major regulator of systemic iron metabolism, while the role of this peptide in the brain has just recently been elucidated. Studies suggest a dual role of hepcidin in neuronal iron-load and inflammation. This is important since neuronal iron-load and inflammation are pathophysiological processes frequently associated with neurodegeneration. Furthermore, manipulation of hepcidin activity has recently been used to recover neuronal damage due to brain inflammation in animal models and cultured cells. Therefore, understanding the mechanistic insights of hepcidin action in the brain is important to uncover its role in treating neuronal damage in neurodegenerative diseases.